2021
DOI: 10.11124/jbies-21-00074
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with lysosomal storage disorders who are receiving enzyme-replacement therapy and the experiences of their family members: a qualitative systematic review

Abstract: The objective of this review was to investigate the experiences of patients with lysosomal storage disorders who are receiving enzyme-replacement therapy and the experiences of their family members.Introduction: Lysosomal storage disorders are rare diseases caused by mutations in the genes that encode proteins required for lysosomal function. The age of onset of these disorders varies from infancy to adulthood, depending on the specific disease and type. Enzyme-replacement therapy is the standard treatment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A previous review of patients with similar rare diseases and their family members showed the burden of symptoms and treatment owing to disease progression. 35 Another review noted the challenges of living as patient with a rare disease and the challenges in the health care system. 36 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous review of patients with similar rare diseases and their family members showed the burden of symptoms and treatment owing to disease progression. 35 Another review noted the challenges of living as patient with a rare disease and the challenges in the health care system. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 33 , 42 In addition, lack of knowledge on the part of health care providers could lead to patient and family concerns. 35 Furthermore, as the disease progresses, patients with leukodystrophy have reduced ADLs and require multiple supports. Patients and families are required to select and combine these support services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Evidence-based information sheets for health professionals
Information sourceThis Best Practice Information Sheet is a summary of evidence derived from a systematic review published in 2022 in JBI Evidence Synthesis. [1] Note: The information contained in this Best Practice Information Sheet must only be used by people who have the appropriate expertise in the field to which the information relates. While care has been taken to ensure that this Best Practice Information Sheet summarizes available research and expert consensus, any loss, damage, cost or expense or liability suffered or incurred as a result of reliance on this information (whether arising in contract, negligence, or otherwise) is, to the extent permitted by law, excluded.
…”
mentioning
confidence: 99%